In vitro and in vivo evaluation of alginate hydrogel-based wound dressing loaded with green chemistry cerium oxide nanoparticles - Zhao, Ran; Zhao, Chenyuyao; Wan, Yi; Majid, Muhammad; Abbas, Syed Qamar; Wang, Yibing (Frontiers in Chemistry, 2023)
Interactive wound dressings have displayed promising outcomes in enhancing the wound healing process. To achieve this, we developed cerium oxide nanoparticles utilizing curcumin as both the reducing and capping agent. Characterization techniques such as SEM, EDX, DLS, Zetasizer, FTIR, and XRD were utilized to analyze the cerium oxide nanoparticles synthesized through a green approach. Interactive wound dressings have shown promising results in promoting the wound healing process. In the present study, we tried to fabricate interactive/bioactive nanocomposite wound dressing with potent antioxidant properties. We fabricated cerium oxide nanoparticles using curcumin as the reducing and capping agent. SEM, EDX, DLS, Zetasizer, FTIR, and XRD were applied to characterize the greensynthesized cerium oxide nanoparticles. The image analysis on the obtained TEM images showed that the curcumin-assisted biosynthesized CeO2NPs have a size of 18.8 ± 4.1 nm. The peaks located at 28.1, 32.7, 47.1, 56.0, 58.7, 69.0, and 76.4 are correspond to (111), ( 200), ( 220), ( 311), ( 222), (400), and (331) crystallographic planes. We applied the Debye-Scherrer equation and observed that the approximate crystallite size of the biosynthesized NPs is around 8.2 nm, based on the most intensive broad Bragg peak at 28.1˚. The cerium oxide nanoparticles synthesized were integrated into an alginate hydrogel matrix, and the microstructure, porosity, and swelling behavior of the resulting wound dressing were assessed. The characterization analyses provided insights into the physical and chemical properties of the green-synthesized cerium oxide nanoparticles and the alginate hydrogel-based wound dressing. In vitro studies demonstrated that the wound dressing based on alginate hydrogel exhibited favorable antioxidant properties and displayed hemocompatibility and biocompatibility. Animal studies conducted on a rat full-thickness skin wound model showed that the alginate hydrogel-based wound dressing effectively accelerated the wound healing process. Overall, these findings suggest that the alginate hydrogel-based wound dressing holds promise as a highly effective material for wound healing applications.The synthesized nanoparticles were incorporated into alginate hydrogel and the microstructure, porosity, and swelling state of the fabricated wound dressing were evaluated. The characterizations revealed the physical and chemical properties of the green-synthesized cerium oxide nanoparticles and the incorporated alginate hydrogel-based wound dressing. .